ผลของฝุ่นละอองที่มีต่ออัตราการซึมผ่านของรังสีไอโซโทป tc-99m dtpa ของปอดตำรวจจราจรในกรุงเทพมหานคร - อุมา เศวตสกุลานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
Particulate matter (PM10) in ambient air in Bangkok metropolis were taken at Pathumwan,Samyan,Victory Monument and Pratunam traffic intersection. The measurement of PM10 average in the morning and afternoon in june to August 1997 and November to January 1998 of Pathumwan police station were 0.28±0.15 and 0.32±0.15 µg/m ….Phyathai police station were 0.45±0.30 and 0.39±0.11 µg/m3respectively. The highest average PM10 was at Victory Monument (0.42±0.29 and 0.40±0.11 µg/m³) The subject and control groups were screened by using questionnaires and interviews about their respiratory conditions. The subject groups were 15 policemen from Pathumwan police station and 15 policemen from Phya Thai police station and the control groups were 10 persons selected from hospital workers. Total medical tests were comducted by chest x-ray, Spirometry and Gamma camera method. Tc-99m DTPA lung clearance in HT-7 and HT-30 between subject and control groups was no significant difference (P<0.05) Tc-99m DTPA lung clearance in HT-7 of traffic policemen from pathumwan and Phya Thai police station were higher than among the control groups (77.1±18.4,70..3±12.3 and 61.1±17.2 minutes, respectively). PM10,chest x-ray and Spirometry were correlated with Tc-99m DTPA lung clearance. Age and exposure time of traffic policemen from Pathumwan and Phya Thai police station were correlated with Tc-99m DTPA lung clearance (r=0.555 and 0.399, respectively)